PENINGKATAN KEKERASAN DAN KETAHANAN AUS PERMUKAAN BESI COR KELABU MELALUI PROSES BORONISASI - Bambang Pratowo; Kunarto Kunarto (JURNAL ILMIAH MOMENTUM, 2011)
The surface hardening process is one of the high temperature treatment precess wich is applied only on the surface of the object of the treatment so that it result an object with superficial hardness without changing the interior matrix shape of the object. The materials used in this reseach are perlitics gray cast iron and low carbon steel wich are easily available an yhe market to increase the hardness and resistance of the surface of the object througt borodisation. As the diffusion material, boron, wich was derived from ferro boron powder was used. The experiment was conducted by veryng temperature of 800 o C and 875 o C, wich the resisting periods of 1 hour, 3 hours, 5 hours. From this experiment, it was expected that there was an increase in hardness and reistance of the object surface without changing its interior matrix shape. After conducting the experiment and some test namely metallography test, hardness test, and resistence test, it showed that there was diffusion process on the surface of the object. Having been compared with the sample before the treatment, it can be seen : Based on the result of the metallgraphy test there is change in the exterior shape of the sample, but a constant interior matrix shape of it. Based on the hardness test, there is an increase on hardness, maximally on the sample caded BCK-5/875 the rate of 1080 HV. Kata kunci : Kekerasan, Aus, Permukaan, Besi Cor, Boronisasi